sEPCR Levels in Chronic Myeloproliferative Diseases and Their Association with Thromboembolic Events: A Case-Control Study - Figen Atalay; Selami Koçak Toprak; Ebru Koca; Sema Karakuş (Turkish Journal of Hematology, 2014)
OBJECTIVE: Venous, arterial, and microcirculatory events are frequently encountered in the clinical course of essential thrombocytosis and polycythemia vera. We aimed to investigate the levels of soluble endothelial protein C receptor (sEPCR) in myeloproliferative diseases to see whether there was a difference between the patients with and without history of thromboembolism. METHODS: The study included patients with polycythemia vera (n=12), patients with essential thrombocytosis (n=13), and controls (n=29). In all groups, we measured proteins C and S, antithrombin and sEPCR levels, and plasma concentrations of thrombin-antithrombin complex, prothrombin fragments 1+2, and D-dimer. RESULTS: Comparing the patients with and without history of thromboembolic attack, statistically significant differences were not observed in terms of sEPCR, D-dimer, thrombin-antithrombin complex, prothrombin fragments 1+2, and hematocrit levels (p=0.318, 0.722, 0.743, 0.324, and 0.065, respectively). CONCLUSION: Significant increase in the parameters that reflect activation of coagulation, such as sEPCR, thrombinantithrombin complex, prothrombin fragments 1+2, and D-dimer, reflects the presence of a basal condition that leads to a tendency toward thrombosis development in ET and PV when compared to healthy controls.